KIRA and the (Maybe) SPACE PRINCESS - Brennan, Megan; Leopard, Whitney; Diaz, Danny; Goodman, Juliet (New York : RH Graphic, 2024)
Kira starts seventh grade at Neo-Earth Junior High school hoping to become a Magical Girl, so to speed up the process she wishes on a shooting star, but instead meets Caticorn, a cat-unicorn space princess with a secret past.
Keywords: Friendship -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Fantasy comic books, strips, etc